Education and Religion in Secular Age from an African Perspective - Paul John Isaak (MDPI AG, 2018)
In this article the author shall argue that before Namibian independence in 1990, Christianity was used by some as a weapon of breaking down, or as a tool of, colonialism, racism, and apartheid. In the name of a religious god unashamed acts of violence and wars were committed and resulted in genocide of 1904 to 1908. However, such brutalities did not conquer the African spirit of what is identified in this article as the Ubuntu (humaneness). Inspired by their sense of Ubuntu the Africans, in the face of German colonialism and the South African imposed Apartheid system, finally emerged victorious and accepted the model of religious pluralism, diversity, and the principle of African Ubuntu. We shall, furthermore, argue that the Namibian educational system and the Namibian Constitution, Articles 1 and 21, the Republic of Namibia is established as a secular state wherein all persons shall have the right to freedom to practise any religion and to manifest such practice. It means religious diversity and pluralism is a value, a cultural or religious or political ideology, which positively welcomes the encounter of religions. It is often characterized as an attitude of openness in a secular state towards different religions and interreligious dialogue and interfaith programs. As an example we shall focus on the subject of Religious and Moral Education where such religious diversity and pluralism are directly linked to political, social, and economic issues, as well as moral values.